Variability of Aerosols and Clouds Over North Indian and Myanmar During the COVID-19 Lockdown Period - Lawand, Divyaja; Bhakare, Sudheer; Fadnavis, Suvarna; Bhawar, Rohini L.; Rahul, P. R. C.; Pallath, Pradeep Kumar; Lolli, Simone (Frontiers in Environmental Science, 2022)
The implementation of a nationwide lockdown to curb the spread of COVID-19 disease has reduced the loading of anthropogenic aerosols. However, AOD distribution over South Asia during the lockdown period shows a dipole pattern i.e. reduction over North Indian and enhancement over the Myanmar region. This dipole pattern is evident in the number of data sets (MODIS, MERRA, and CALIPSO). MODIS fire counts collocated with CALIPSO smoke aerosols show enhancement over Myanmar indicating the contribution from fires. However, over the North India region numbers of fires during the lockdown period are less than climatology thus, the observed reduction in AOD is due to fires and anthropogenic sources. Our analysis shows that aerosols originating from biomass burning forms a layer (900-600 hPa) over the Myanmar region that produces atmospheric heating (0 – 2.8 K/day) that eventually leads to cloud dissipation/burning (negative in-atmospheric cloud radiative forcing ~ -13 W/m2) and precipitation reduction ( -1 to -4 mm) over Myanmar. While, the aerosol reduction over North India favors cloud formation, i.e. increase in cloud cover and reduction in specific cloud liquid water content leading to precipitation enhancement indicating the anti-Twomey effect.